2011
DOI: 10.1177/1468087411412033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of design and operating parameters on the ion current in a single-cylinder diesel engine

Abstract: Ion current has been the subject of extensive research in gasoline engines for in-cylinder combustion sensing and as a feedback signal for closed-loop engine control. The sources of the ion current in gasoline engines have been identified. Such identification is not the case in diesel engines. This paper presents experimental data and analysis of the ion current produced in a single-cylinder diesel engine equipped with an electronically controlled common-rail-injection system using an accessible engine control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…According to the definition of the Gaussian function and equation ( 3 For a given data group (x 1 , y 1 ), (x 2 , y 2 ), ., (x n , y n ) which accord with the Gaussian distribution, the Gaussian function is expressed as equation (2), where a, b and g are unknown parameters which need to be obtained.…”
Section: Parameterization Of the Ion Current With Gaussian Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the definition of the Gaussian function and equation ( 3 For a given data group (x 1 , y 1 ), (x 2 , y 2 ), ., (x n , y n ) which accord with the Gaussian distribution, the Gaussian function is expressed as equation (2), where a, b and g are unknown parameters which need to be obtained.…”
Section: Parameterization Of the Ion Current With Gaussian Functionsmentioning
confidence: 99%
“…The ion current method using a spark plug as the sensor has attracted much attention owing to its rapid response, low cost and convenience. [1][2][3][4][5][6] There have been many reports on the applications of the ion current method to an online survey of SI engines. Daniels et al 7 investigated partial-burn detection using an ionization current and noted that a light partial burn, which is difficult to observe using the pressure method, can be detected only by the ionization current.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the engine is running under EGR conditions, the ion current signal is weakened due to the decrease in combustion temperature, but the correlation between the ion current signal and the combustion parameters is still as high as 0.9 [38]. On the natural gas engines and diesel engines, it is also found that the correlation between ion current signal and combustion parameters is higher than 0.9 [39,40]. In addition, on the HCCI engine, the experimental results of Johansson et al [41] show that the correlation coefficient of the ion current characteristic parameter and CA50 is 0.877, so the ion current signal can be used to estimate the combustion phase of HCCI.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, Yoshiyama et al 31 designed multiple ion sensors to obtain the ion current in an SI engine, and found that the peak location of the ion current is close to the peak location of heat release calculated from the measured cylinder pressure under all engine operating modes. Furthermore, Badawy et al 32 presented experimental data and analysis of the ion current produced in a single-cylinder diesel engine equipped with an electronically controlled common-rail-injection system using an accessible engine control unit, and the correlation coefficients between combustion parameters and the ion current were investigated. However, further research is still needed to find a more accurate parameter for the pressure characteristic correlation.…”
Section: Introductionmentioning
confidence: 99%